Melatonin for the treatment of gastrointestinal disorders: an overview. (2nd April 2021) - Mantle, David; Smits, Marcel G
Abstract : Conventional pharmacological agents for the treatment of common (10–25% prevalence) gastrointestinal disorders may be associated with significant adverse effects in some patients. Therefore, there is a rationale to develop alternative therapeutic strategies for such individuals. This article reviews the evidence for the use of supplemental melatonin—a substance with an excellent safety record, free of significant adverse effects—in the management of gastro-oesophageal reflux disease, gastritis, irritable bowel syndrome and ulcerative colitis.